Subcutaneous Fat Triacylglycerols Profile from Iberian Pigs as a Tool To Differentiate between Intensive and Extensive Fattening Systems - Gallardo, Emerenciana; Narváez-Rivas, Monica; Pablos, Fernando; Jurado, J. Marcos; León-Camacho, Manuel (Journal of Agricultural and Food Chemistry, 2012)
Triacylglycerols of subcutaneous fat of Iberian pigs reared on two different feeding systems, extensive and intensive, have been determined by gas chromatography with a flame ionization detector. Analyses were performed on a column coated with a bonded stationary phase (50% phenyl?50% methylpolysiloxane) with hydrogen as the carrier gas. Lipids were extracted by melting the subcutaneous fat in a microwave oven and then filtering and dissolving in hexane. A total amount of 1995 samples from several campaigns were considered. Palmitoyl-stearyl-oleoyl glycerol and palmitoyl-dioleoyl glycerol were the most abundant triacylglycerols found in the samples. A study on the discriminating power of the triacylglycerols to differentiate samples according to the pig feeding system was performed. By using the triacylglycerols as chemical descriptors, principal component analysis, linear discriminant analysis, and soft independent modeling of class analogy were applied. Dioleoyl-linoleoyl glycerol and oleoyl-dilinoleoyl glycerol were the most discriminating variables. Variable?variable plots of these two glycerols allow separation of the samples according to their content.
doi: 10.1021/jf2045312doi: 10.1021/jf2045312The following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: gas chromatography; iberian pig; pattern recognition; subcutaneous fat; triacylglycerols

Acorn (Quercus spp.) fruit lipids: Saponifiable and unsaponifiable fractions: A detailed study - León-Camacho, Manuel; Viera-Alcaide, Isabel; Vicario, Isabel M. (Journal of the American Oil Chemists' Society, 2004)
The composition of the oils extracted from the acorn fruit of three species of Mediterranean oaks, Quercus ilex L., Q. suber L., and Q. faginea L., was characterized. Both major and minor components, including FA, TG, sterols, methyl sterols, triterpenic and aliphatic alcohols, tocopherols, and hydrocarbons, were identiﬁed by standard methods and MS. Highresolution GLC and HPLC were used for quantiﬁcation. The FA profile, together with the equivalent carbon numbers and TG carbon numbers, was compared with data for other edible vegetable oils. Oil yield, expressed as wet weight, was 5% (w/w). Sterol content was remarkable for the three species (8,563–11,420 mg/kg), with β-sitosterol being the most abundant (80%). Oils were also high in tocopherol, with a wide variation between species (165–456 mg/kg) but with γ-tocopherol predominating in all three oils (90% of the total tocopherol content). Also, high terpenic alcohol contents were found (1527–2984 mg/kg), with dammaradienol and β-amyrin being the most abundant (33–60% of the total alcohol content). Bioactive properties and industrial applications of this underutilized native product are also discussed.
Keywords: Acorn oil; fatty acid; hydrocarbons; Quercus spp.; sterols; triglycerides